Lattice Boltzmann simulation of alumina-water nanofluid in a square cavity - He, Yurong (Springer, 2011)
A lattice Boltzmann model is developed by coupling the density (D2Q9) and the temperature distribution functions with 9-speed to simulate the convection heat transfer utilizing Al(2)O(3)-water nanofluids in a square cavity. This model is validated by comparing numerical simulation and experimental results over a wide range of Rayleigh numbers. Numerical results show a satisfactory agreement between them. The effects of Rayleigh number and nanoparticle volume fraction on natural convection heat transfer of nanofluid are investigated in this study. Numerical results indicate that the flow and heat transfer characteristics of Al(2)O(3)-water nanofluid in the square cavity are more sensitive to viscosity than to thermal conductivity.